Perilaku Berzakat di Masa Pandemi Covid-19 - Rodame Monitorir Napitupulu; Rini Hayati Lubis; Fahrina Putri Sapna (ITB AAS INDONESIA Surakarta, 2021)
The impact of the pandemic COVID-19 resulted in the weakening of the State economy causing a decrease in individual income, in contrast to the collection of zakat during the pandemic increased, the increase in zakat funds is inseparable from the behavior of muzakki, then from the purpose in the study how muzakki behavior in paying their zakat during the pandemic COVID-19, and how the response or response muzakki to the management of BAZNAS this study explored the approach of mix method with random sampling techniques numbered 396 respondents. The data was obtained based on the results of an online questionnaire through a google form. The results of this study showed that the behavior of charity during the pandemic COVID-19 does not affect in giving zakat even though it is in the red zone, in all respondents have done zakat, especially zakat fitrah which is often done in the month of Ramadan, as for zakat payments made in mosques or directly. However, the majority muzakki paid zakat through zakat institution because of credibility, transparency, and accountability reason.